FLOWER ONTOGENY AND REPRODUCTIVE BIOLOGY OF SALVIA VIRIDIS L. - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2017)
The flower ontogeny and the developmental features of male and female gametophyte were investigated in Salvia viridis L. It has purple and hermaphrodite flowers. The stamen primordia differantiate shortly before the initiation of carpel primordia from floral meristem. The anther is bisporangiate. Although the anter wall consists of an epidermis, endothecium, middle layer and secretory tapetum in young stage, only epidermal and endothecial cells preserve their vitality until the period of anther dehisce. The microspore tetrad is tetrahedral and the mature pollen grains are pericolpate and tectatae. The pistil has a superior ovary with four loculi and a thick, closed style with forked, unpapillate stigma. The anatropous, tenuinucellate ovule differentiates by axilar placentation. The development of the monosporic embryo sac follows by the Polygonum type.
Keywords: Developmental biology; Ontogeny; Reproductive biology; Salvia viridis; Sexual reproduction; LAMIACEAE; POLLEN